1997
DOI: 10.1128/mcb.17.1.170
|View full text |Cite
|
Sign up to set email alerts
|

Lack of a Role for Jun Kinase and AP-1 in Fas-Induced Apoptosis

Abstract: Cross-linking of Fas (CD95) induces apoptosis, a response that has been reported to depend upon the Ras activation pathway. Since many examples of apoptosis have been reported to involve AP-1 and/or the AP-1-activating enzyme Jun kinase (JNK), downstream effectors of Ras or Ras-like small GTP-binding proteins, we evaluated the role of these molecules in Fas-mediated apoptosis. Although cross-linking of Fas on Jurkat T cells did result in JNK activation, increased activity was observed relatively late, being de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
158
4
1

Year Published

1997
1997
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(181 citation statements)
references
References 75 publications
18
158
4
1
Order By: Relevance
“…Fasand tumor necrosis factor-mediated apoptosis). 40,41 The mechanism by which JNK becomes activated in response to apoptotic signals is not completely understood. JNK activity is regulated by specific kinases (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Fasand tumor necrosis factor-mediated apoptosis). 40,41 The mechanism by which JNK becomes activated in response to apoptotic signals is not completely understood. JNK activity is regulated by specific kinases (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Fas-induced apoptosis of Jurkat T cells was reported to be mediated by the JNK/p38 MAPK pathway downstream of Rac (Brenner et al, 1997). In contrast, the activation of JNK and p38 MAPK accompanied by Fas-mediated cell death was shown to occur downstream of caspases (Juo et al, 1997) and thus is not considered to be a critical event (Lenczowski et al, 1997;Nagata, 1997). Rather, the JNK pathway mediates survival signals in T cells (Nishina et al, 1997).…”
Section: Phosphorylation Of Threonine-308 and Serine-473 Is Critical mentioning
confidence: 99%
“…It has been shown that in many cases, apoptosis correlates with the stimulation of the stress activated MAP kinases SAPK/ JNK and p38 (reviewed in Schulze-Ostho et al, 1998), which are downstream targets of Cdc42Hs and Rac1 (Coso et al, 1995;Minden et al, 1994). However, numerous cases of apoptosis occurring independently of JNK activation have also been described (Khwaja and Lenczowski et al, 1997;Liu et al, 1996).…”
Section: Introductionmentioning
confidence: 99%